Pendampingan Penyusunan Instrumen Penilaian Creative Problem-Solving Berbasis Ethno-Edutainment Untuk Pembelajaran Mendalam - Ulya, Himmatul; Ardianti, Sekar Dwi; Rahayu, Ratri (Universitas Muhammadiyah Mataram, 2026)
Abstract: The main problems faced by partners include teachers' low ability to develop assessment instruments that are suitable for deep learning and 21st century-oriented learning, and teachers' suboptimal integration of local cultural values into assessment. This activity aims to improve teachers' ability to develop ethno-edutainment-based creative problem-solving (CPS) assessment instruments for deep learning and equip teachers with the skills to integrate local culture into assessment through the ethno-edutainment approach. The activity was carried out through the stages of planning, socialization, mentoring, simulation, and evaluation with a participatory and active learning approach. Teachers were provided with deep learning materials, CPS instruments, and ethno-edutainment applications, then directly assisted in developing and presenting locally-based assessment instruments. The results of the activity showed a significant increase in teacher competence, where the average ability of teachers in developing CPS assessment instruments for deep learning increased from 54% at the initial stage to 83.2% after the activity, while the ability to integrate local cultural values into assessment increased from 52.2% to 85.2%. These results indicate that assistance in developing ethno-edutainment-based CPS instruments is effective in improving the professional competence of elementary school teachers.Abstrak: Permasalahan utama mitra meliputi rendahnya kemampuan guru dalam menyusun instrumen penilaian yang sesuai dengan pembelajaran mendalam dan berorientasi abad 21 dan belum optimalnya guru dalam mengintegrasikan nilai budaya lokal dalam penilaian. Kegiatan ini bertujuan meningkatkan kemampuan guru dalam menyusun instrumen penilaian creative problem-solving (CPS) berbasis ethno-edutainment untuk pembelajaran mendalam dan membekali guru dengan keterampilan mengintegrasikan budaya lokal dalam penilaian melalui pendekatan ethno-edutainment. Kegiatan dilaksanakan melalui tahapan perencanaan, sosialisasi, pendampingan, simulasi, dan evaluasi dengan pendekatan partisipatif dan active learning. Guru dibekali materi pembelajaran mendalam, instrumen CPS, serta penerapan ethno-edutainment, kemudian didampingi secara langsung dalam menyusun dan mempresentasikan instrumen penilaian berbasis budaya lokal. Hasil kegiatan menunjukkan peningkatan signifikan kompetensi guru, di mana rata-rata kemampuan guru dalam menyusun instrumen penilaian CPS pembelajaran mendalam meningkat dari 54% pada tahap awal menjadi 83,2% setelah kegiatan, sedangkan kemampuan mengintegrasikan nilai budaya lokal dalam penilaian meningkat dari 52,2% menjadi 85,2%. Hasil ini menunjukkan bahwa pendampingan penyusunan instrumen CPS berbasis ethno-edutainment efektif dalam meningkatkan kompetensi profesional guru sekolah dasar.